Isolation of lingzhifuran A and lingzhilactones D–F from Ganoderma lucidum as specific Smad3 phosphorylation inhibitors and total synthesis of lingzhifuran A. Issue 81 (16th August 2016) - Ding, Wei-Yi; Ai, Jun; Wang, Xin-Long; Qiu, Fayang G.; Lv, Qing; Fang, Ping; Hou, Fan-Fan; Yan, Yong-Ming; Cheng, Yong-Xian
Abstract : Lingzhifuran A (1 ) and lingzhilactones D–F (2–4 ), four new phenolic meroterpenoids were isolated from the fruiting bodies of Ganoderma lucidum . Total synthesis and biological evaluation of lingzhifuran A were carried out herein. Abstract : Lingzhifuran A (1 ) and lingzhilactones D–F (2–4 ), four new phenolic meroterpenoids were isolated from the fruiting bodies of Ganoderma lucidum . Their structures were identified by spectroscopic data. Chiral HPLC analysis indicates the racemic nature of2–4 . Chiral separation followed by X-ray diffraction analysis discloses the absolute configuration of (−)-2 . Compounds1 and2 could selectively inhibit TGF-β1-induced Smad3 phosphorylation in rat renal tubular epithelial cells, representing novel scaffolds of selective Smad3 activation inhibitors. Total synthesis accompanied by in vivo rodent experiments reveals antifibrotic activities of1 against kidney fibrosis. Finally, a plausible biosynthetic pathway for1 was proposed.